Indonesian Version of the Fear of COVID-19 Scale: Validity and Reliability - Mohd Amiruddin Mohd Kassim; Friska Ayu; Assis Kamu; Pang, Nicholas Tze Ping; Chong Mun Ho, Chong Mun; Hafid Algristian; Moch Sahri; Nurfarah Lydia Hambali; Azizan Omar (Universiti Malaysia Sabah, 2020)
The Fear of COVID-19 Scale (FCV-19S) is a seven-item uni-dimensional scale assessing the severity of COVID-19 concerns. A translation and validation of the FCV-19S in Bahasa Indonesia language was expedited in view of the worrying trends of COVID-19 in Indonesia as well as its psychological squeal. Formal WHO forward and backward translation sequences were applied in translating the English FCV-19S into Bahasa Indonesia. Indonesian university participants were recruited viaconvenience sampling online using snowball methods. The reliability and validity of the Indonesian FCV-19S was psychometrically evaluated by applying confirmatory factor analysis and Rasch analysis in relation to sociodemographic variables and response to the depression, anxiety, and stress components of the Indonesian version of DASS-21. The sample consisted of 434 Indonesian participants. The Cronbach α value for the Indonesia FCV-19-I was 0.819 indicated very good internal reliability. The results of the confirmatory factor analysis showed that the uni-dimensional factor structure of the FCV19S fitted well with the data. The FCV-19-I was significantly correlated with anxiety (r=0.705, p<0.001) subscales of DASS-21. The FCV-19-I’s properties tested using Rasch analysis were also satisfactory, although three items in FCV-19-I were not able to be tested. Hence, the Indonesian FCV-19-I is valid and reliable, with robust psychometric properties from classical and modern psychometric methods. It can be a valuable and useful tool in identifying and responding topsychological distress caused by COVID-19.